Immunotherapy: breaching the barriers for cancer treatment. (19th August 2019) - Martinez, Victor G.; Park, Danielle; Acton, Sophie E.
Abstract : The great ambition to treat cancer through harnessing a patient's own immune responses has started to become reality. Clinical trials have shown impressive results and some patients reaching the end of existing treatment options have achieved full remission. Yet the response rate even within the most promising trials remain at just 30–40% of patients. To date, the focus of immunotherapy research has been to identify tumour antigens, and to enhance activation of effector lymphocytes. Yet this is only the first step to effective immunotherapy for a broader range of patients. Activated cytotoxic T cells can only act on their tumour cell targets if they have free and easy access to all tumour regions. Solid tumours are complex, heterogeneous environments which vary greatly in their physical properties. We must now focus our efforts on understanding how factors such as the composition, density and geometry of tumour extracellular matrix acts to impede or promote immune cell infiltration and activation, and work to design novel pharmacological interventions which restore and enhance leucocyte trafficking within solid tumours. This article is part of a discussion meeting issue 'Forces in cancer: interdisciplinary approaches in tumour mechanobiology'.